PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK MENGGUNAKAN ZOOM MEETING DI ERA PANDEMI COVID 19 - Simbolon, Erikson; Alloysia, Mahavira Ega; Fajariyanto, Tri Chandra (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2022)
The study was conducted to analyze how the shaping of honest character and the responsibility of learners in the process of Catholic High School Deli Murni, Medan. This study demonstrates that 1) learners can learn and work on tasks independently through learning videos and power points given by teachers and honest learners can be seen when they are active in the proven learning by asking, the teacher must respond in teaching, having teachers repeat the given material, 2) the responsibility of learners in learning seen through the zoom application meeting is seen as learners come into zoom meetings without being late, giving assignments on time, using modest clothing during the study and carrying out prayer switch schedules both before and after class. Implementation of the Catholic learning process in zoom meetings is seen when 3) teachers begin learning with a conception activity of opening prayer, greeting learners and missionaries to see readiness for lessons. 4) the teacher's core activity shares the material screen with learners and allows learners to ask about given material. 5) the end of the teacher's learning gives conclusions and duties to learners as reflections during the learning process.